2012
DOI: 10.1177/0883073812460917
|View full text |Cite
|
Sign up to set email alerts
|

Compensated Dyslexics Have a More Efficient Error Detection System Than Noncompensated Dyslexics

Abstract: Error/correct-related negativities, response-locked components of the evoked response potential, and N100, a stimulus-locked component, were used to compare error detection monitoring in skilled readers and in compensated and noncompensated dyslexic adolescent readers during a lexical decision task. Results showed a general increase in N100 amplitudes prior to error commission in all groups; a significant decrease in error/correct-related negativity amplitudes in the noncompensated dyslexics compared with the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
32
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 15 publications
(42 citation statements)
references
References 43 publications
(73 reference statements)
8
32
2
Order By: Relevance
“…Our results of increased ERN after the RAP training correspond with a previous study showing increased ERN and improved reading in children with dyslexia and typical readers following 8 weeks of the RAP training in Hebrew (Horowitz‐Kraus & Breznitz, ). Interestingly, the difference in ERN size in that study decreased from 2.4 μV before intervention to 0.56 μV after the RAP training, as opposed to a greater decrease from 3.38 to 0.084 μV in the current study.…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…Our results of increased ERN after the RAP training correspond with a previous study showing increased ERN and improved reading in children with dyslexia and typical readers following 8 weeks of the RAP training in Hebrew (Horowitz‐Kraus & Breznitz, ). Interestingly, the difference in ERN size in that study decreased from 2.4 μV before intervention to 0.56 μV after the RAP training, as opposed to a greater decrease from 3.38 to 0.084 μV in the current study.…”
Section: Discussionsupporting
confidence: 90%
“…The reading acceleration manipulation used in this study has been found to increase attention span, reduce distractibility (Breznitz, ; Breznitz, ) and enhance working‐memory processing during reading (Breznitz & Share, ; Breznitz et al, ; Horowitz‐Kraus & Breznitz, ; Horowitz‐Kraus et al, ). The reading acceleration manipulation has been shown to have a positive effect on neural circuits related to reading and executive control, as well as behavioural improvement in reading in children.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations